Internet security using biometrics - Tiwari S.; Singh A.; Singh R.S.; Sanjay K. (My University, 2025)
Internet security is a big challenge for Internet users, and passwords are the primary means of authenticating users. Establishing identity is becoming difficult in this vastly interconnected society. The need for reliable Internet security techniques has increased in the wake of heightened concerns about security and rapid advancements in networking, communication, and mobility. Biometrics is the science of identifying an individual based on his physical (static) or behavioral (dynamic) characteristics, and it is beginning to gain acceptance as a legitimate method for determining an individual's identity. Biometrics has been used for many years in high security government and military applications, but the technology is now becoming affordable for use as an authentication methods and general security feature. In this chapter, the authors provide an overview of Internet security using Biometrics. © 2012, IGI Global.